2021
DOI: 10.3390/cancers13051028
|View full text |Cite
|
Sign up to set email alerts
|

CENPE Inhibition Leads to Mitotic Catastrophe and DNA Damage in Medulloblastoma Cells

Abstract: Medulloblastoma (MB) is the most frequent brain tumor in children. The standard treatment consists in surgery, followed by radiotherapy and chemotherapy. These therapies are only partially effective since many patients still die and those who survive suffer from neurological and endocrine disorders. Therefore, more effective therapies are needed. Primary microcephaly (MCPH) is a rare disorder caused by mutations in 25 different genes. Centromere-associated protein E (CENPE) heterozygous mutations cause the MCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…A molecule that selectively inhibits KIF14 ATPase activity was identified in a screen of small molecules [ 141 ]. Ultimately, a plethora of different molecules have been proposed as CENPE inhibitor: Syntelin, PF-2771, and Compound-A were shown to inhibit CENPE motor domain [ 107 109 ]; but the most promising molecule is GSK923295 that has already finished phase I clinical trial for other types of cancers [ 110 ] and it was shown to be effective in MB [ 106 ]. In conclusion, inhibition of KNL1, CENPE, ASPM, CITK, and KIF14 may mimic the effects of MTAs on cell division but could work with particular effectiveness on brain tumor cells, underscoring the importance of developing specific inhibitors and test them in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A molecule that selectively inhibits KIF14 ATPase activity was identified in a screen of small molecules [ 141 ]. Ultimately, a plethora of different molecules have been proposed as CENPE inhibitor: Syntelin, PF-2771, and Compound-A were shown to inhibit CENPE motor domain [ 107 109 ]; but the most promising molecule is GSK923295 that has already finished phase I clinical trial for other types of cancers [ 110 ] and it was shown to be effective in MB [ 106 ]. In conclusion, inhibition of KNL1, CENPE, ASPM, CITK, and KIF14 may mimic the effects of MTAs on cell division but could work with particular effectiveness on brain tumor cells, underscoring the importance of developing specific inhibitors and test them in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“… MCPH 4 KNL1 Kinetochore scaffold 1 Binds microtubules at the kinetochore by two distinct microtubule-binding regions at N-terminal [ 61 ] Chromosome misalignment, no microtubule-kinetochore attachment, and multinucleated cell formation [ 59 , 60 ] KNL1 knockdown decreases the proliferation and cloning ability of GBM cells [ 65 ] MCPH 5 ASPM Abnormal spindle-like, microcephaly-associated protein Controls the number and length of astral microtubules and microtubule disassembly at spindle poles [ 71 , 72 ] Altered spindle orientation, cytokinesis failure, apoptosis [ 67 , 70 , 71 ] ASPM loss impairs GBM and MB tumor growth and increases DNA damage [ 50 , 77 80 ] MCPH 13 CENPE Centromere-associated protein E Microtubule motor protein. Promotes microtubule elongation at kinetochore and controls the length of astral microtubules [ 98 103 ] Chromosome misalignment, no microtubule-kinetochore attachment, altered spindle orientation, mitotic arrest [ 92 94 ] CENPE inhibition reduces proliferation of GBM and MB cells, increases DNA damage and induces mitotic catastrophe [ 105 , 106 ] MCPH 17 CIT Citron Rho-interacting serine/threonine kinase Controls the number and length of astral microtubules and promotes microtubule stabilization at midbody [ 71 , 124 ] Altered spindle orientation, cytokinesis failure, apoptosis [ 120 , 126 ] CITK loss impairs MB tumor growth, increases DNA damage and the sensitivity to radiation and cisplatin …”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…CENPE is required for capturing spindle MTs and attachment to the kinetochores [ 102 , 103 ]. Defects in the organization of spindle MTs and delayed progression of the mitosis, leading to abnormal exit from mitosis have been described in MCPH13 patient-derived cell lines as well as in medulloblastoma [ 101 , 104 ]; the presence of binucleate cells of unequal size suggests that, in the absence of CENPE, chromosome segregation and cytokinesis fails [ 101 , 104 ]. Knockout of Cenpe in mice is embryonic lethal, however, in conditional mutants, severe mitotic chromosome misalignment and chromosome segregation fails, in accordance with the observations in human cells [ 105 , 106 ].…”
Section: Mcph Genesmentioning
confidence: 99%